Dating violence and physical health: A longitudinal lens on the significance of relationship dynamics and anti‐social lifestyle characteristics. (October 2016) - Copp, Jennifer E.; Giordano, Peggy C.; Longmore, Monica A.; Manning, Wendy D.
Abstract: Background: Scholars have documented the significant physical health consequences of intimate partner violence. Yet, because existing research draws primarily on clinical samples of adult women, it is unclear whether exposure to dating violence is related to health detriments among young men and women. Furthermore, data limitations largely have precluded consideration of the mechanisms underlying these previously observed associations. Aims: We sought to examine the direct association between dating violence and self‐rated physical health during adolescence and across the transition to adulthood. We also directed attention to potential mediating and confounding factors, including negative relationship dynamics, anti‐social lifestyle characteristics and physical health correlates. Methods: Drawing on five waves of data from the Toledo Adolescent Relationships Study (n = 3746 person‐periods), we used growth curve analyses to examine these associations among a sample of young men and women in dating relationships. Results: Longitudinal analyses revealed that dating violence was associated with declines in self‐rated physical health across the period from adolescence to young adulthood. This effect, however, was attenuated with the inclusion of negative relationship dynamics. Conclusions: Findings suggest the need to further examine the physical health consequences of dating violence, with a particular focus on the relationship context and other potential confounding forces. Copyright © 2016 John Wiley & Sons, Ltd.